Trade intensity and output synchronisation: On the endogeneity properties of EMU - Guglielmo Maria Caporale; Roberta De Santis; Alessandro Girardi (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Using annual bilateral data over the period 1988-2011 for a panel of 24 industrialised and emerging economies, we analyse in a time-varying framework the determinants of output synchronisation in EMU (European Monetary Union) distinguishing between core and peripheral member states. The results support the specialisation paradigm rather than the endogeneity hypothesis. Evidence is found in the euro period of diverging patterns between the core and the peripheral EMU countries raising questions about the future stability of EMU.
Keywords: F10; F15; F17; F4; 330; output synchronisation; trade intensity; endogeneity; European Monetary Union (EMU)